Inclusive learning innovation with mobile-based bilingual interactive games for slow learner students - Suastika Yulia Riska; Widya Adhariyanty Rahayu; Abdul Aziz Muslim (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
This Community Service Program developed a mobile-based bilingual interactive game called "Safari Kingdom" for slow learner students in inclusive education. The purpose of this service is to improve the language and cognitive skills of slow-learner students in an inclusive educational environment. The method used is CBPR (Community-Based Participatory Research) which develops games in collaboration with teachers, students, and lecturers in designing innovative learning media that supports students' language and cognitive skills. The development process includes prototyping, initial trials, and ongoing evaluation with feedback from stakeholders. The results of the implementation show that the use of this game has a positive impact on the understanding of slow-learner students in bilingual learning, increase learning motivation, and assists teachers in integrating technology into teaching methods. The average quiz score of students increased from 43.6 in conventional learning to 84.6 after using the game. A questionnaire of teachers and guardians of students revealed that 90 percent agreed that the use of games increased learning motivation, while 95 percent supported the effectiveness of mobile game-based learning. The program successfully integrates technology into more inclusive and interactive teaching methods.